Effect of whole-body vibration therapy on performance recovery - Manimmanakorn, N.; Ross, J. J.; Manimmanakorn, A.; Lucas, S. J. E.; Hamlin, M. J. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To compare whole-body vibration (WBV) with traditional recovery protocols after a high-intensity training bout. Methods: In a randomized crossover study, 16 athletes performed 6 × 30-s Wingate sprints before completing either an active recovery (10 min of cycling and stretching) or WBV for 10 min in a series of exercises on a vibration platform. Muscle hemodynamics (assessed via near-infrared spectroscopy) were measured before and during exercise and into the 10-min recovery period. Blood lactate concentration, vertical jump, quadriceps strength, flexibility, rating of perceived exertion (RPE), muscle soreness, and performance during a single 30-s Wingate test were assessed at baseline and 30 and 60 min postexercise. A subset of participants (n = 6) completed a 3rd identical trial (1 wk later) using a passive 10-min recovery period (sitting). Results: There were no clear effects between the recovery protocols for blood lactate concentration, quadriceps strength, jump height, flexibility, RPE, muscle soreness, or single Wingate performance across all measured recovery time points. However, the WBV recovery protocol substantially increased the tissue-oxygenation index compared with the active (11.2% ± 2.4% [mean ± 95% CI], effect size [ES] = 3.1, and -7.3% ± 4.1%, ES = -2.1 for the 10 min postexercise and postrecovery, respectively) and passive recovery conditions (4.1% ± 2.2%, ES = 1.3, 10 min postexercise only). Conclusion: Although WBV during recovery increased muscle oxygenation, it had little effect in improving subsequent performance compared with a normal active recovery.